Lost Treasures : Hondo - Book 1 - L'Amour, Louis 1908- (New York : Bantam Books, 1997)
In the aftermath of an Apache uprising, Hondo Lane, a U.S. Cavalry dispatcher tries to convince Angie Low and her son, Johnny, to leave their isolated ranch and flee with him to safety.
Originally published: New York : Fawcett Books, 1953.
Keywords: Western